Lavender Aromatherapy and Sleep Quality among Perimenopausal Women in a Primary Health Care Setting in South Jakarta - Puji Hastutiningsih; Putri Azzahroh; Rukmaini (International Health Sciences Journal, 2026)
Sleep disturbances are common among perimenopausal women due to hormonal fluctuations and psychosocial changes, which may negatively affect physical health, emotional well-being, and overall quality of life. Non-pharmacological interventions are increasingly recommended in primary health care settings to manage sleep problems safely and effectively. This study aimed to examine the relationship between lavender aromatherapy and sleep quality among perimenopausal women in a primary health care setting. A quasi-experimental study with a pretest–posttest control group design was conducted involving 60 perimenopausal women aged 45–55 years who were divided into an intervention group (n = 30) and a control group (n = 30). Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). The intervention group received lavender aromatherapy via inhalation using a diffuser for 30 minutes before bedtime over seven consecutive days, while the control group received no aromatherapy intervention. Data were analyzed using the Wilcoxon Signed-Rank Test and the Mann–Whitney U Test. The results showed a significant improvement in sleep quality in the intervention group, with the mean PSQI score decreasing from 12.00 (SD = 1.89) to 6.23 (SD = 2.73) (p < 0.001), whereas no significant change was observed in the control group (p = 0.349). Posttest comparison revealed a significant difference in sleep quality between the intervention and control groups (p < 0.001). In conclusion, lavender aromatherapy is associated with improved sleep quality among perimenopausal women and may serve as an effective complementary intervention in primary health care settings.